Intracoronary vs intravenous bivalirudin bolus in ST-elevation myocardial infarction patients treated with primary angioplasty. Issue 5 (September 2016) - Lupi, Alessandro; Rognoni, Andrea; Cavallino, Chiara; Secco, Gioel G; Reale, Danilo; Cossa, Giuseppe; Rosso, Roberta; Bongo, Angelo S; Cortese, Bernardo; Angiolillo, Dominick J; Jaffe, Allan S; Porto, Italo
Background: Intracoronary bolus administration may provide high local bivalirudin concentration without changing the global dose, potentially offering a more favorable antithrombotic effect in the infarct related artery (IRA). Objectives: The purpose of this study was to investigate the feasibility and safety of intracoronary bolus administration of bivalirudin followed by the standard intravenous infusion in ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). Methods: In 245 consecutive patients treated with primary PCI, bivalirudin bolus was given directly in the IRA, followed by a standard intravenous infusion. Clinical reperfusion markers, postprocedural coronary flow indexes, and bleeding events of the intracoronary group were compared with a propensity score-matched cohort of primary PCI patients ( n =245) treated with the standard bivalirudin protocol of intravenous bolus and infusion. Results: Higher rates of ⩾70% ST-segment resolution (72.7% vs 60.0%, p =0.004), lower postprocedural peak CK-MB levels (188.3±148.7 vs 242.1±208.1 IU/dl, p =0.025) and better Thrombolysis in Myocardial Infarction (TIMI) frame count values (14.7 vs 17.9, p =0.001) were observed in the IC bolus group compared with the standard intravenous bolus group. Rates of bleeding were similar between groups. Only three cases of acute stent thrombosis were observed, all in the intravenous bolus group ( p =0.25). Conclusions: Intracoronary bivalirudin bolus administration during primary PCI is safe and improves ST-segment resolution, postprocedural coronary flow and enzymatic infarct size compared with the standard intravenous route.